Contribution of Functional Divergence Through Copy Number Variations to the Inter-Species and Intra-Species Diversity in Specialized Metabolites - Shirai, Kazumasa; Hanada, Kousuke (Frontiers in Plant Science, 2019)
There is considerable diversity in the specialized metabolites within a single plant species (intra-species) and among different plant species (inter-species). The functional divergence associated with gene duplications largely contributes to the inter-species diversity in the specialized metabolites, whereas the intra-species diversity is due to gene dosage changes via gene duplications [i.e., copy number variants (CNVs)] at the intra-species level of evolution. This is because CNVs are thought to undergo associated with less functional divergence at the intra-species level of evolution. However, functional divergence caused by CNVs may induce specialized metabolite diversity at the intra-species and inter-species levels of evolution. We herein discuss the functional divergence of CNVs in metabolic quantitative trait genes (mQTGs). We focused on 5,654 previously identified mQTGs in 270 Arabidopsis thaliana accessions. The ratio of nonsynonymous to synonymous variations tends to be higher for mQTGs with CNVs than for mQTGs without CNVs within A. thaliana accessions, suggesting that CNVs are responsible for the functional divergence among mQTGs at the intra-species level of evolution. To evaluate the contribution of CNVs to inter-species diversity, we calculated the ratio of nonsynonymous to synonymous substitutions in the Arabidopsis lineage. The ratio tends to be higher for the mQTGs with CNVs than for the mQTGs without CNVs. Additionally, we determined that mQTGs with CNVs are subject to positive selection in the Arabidopsis lineage. Our data suggest that CNVs are closely related to functional divergence contributing to adaptations via the production of diverse specialized metabolites at the intra-species and inter-species levels of evolution.